A review on the pathogenesis theory of cancerous toxin from the viewpoint of system theory - Tianhao Guo; Hongguang Zhou; Fangping Chen; Yutian Gu; Liu Li; Haibo Cheng (Science of Traditional Chinese Medicine)
Abstract. In recent years, traditional Chinese medicine (TCM) has made great progress in the prevention and treatment of cancer. It has gradually revealed its characteristics and advantages in clinical practice, including alleviating clinical symptoms, prolonging survival time, decreasing the adverse effects of chemotherapy, and improving living quality. However, clinical TCM treatment of cancer lacks systematic theoretical guidance, because ancient TCM has not formed a recognized theoretical system of cognitive cancer, and there still are different opinions on the pathogenesis of cancer. Due to the complexity of cancer, the essence of cancer pathogenesis has not been described accurately by using common pathogenic factors, such as pathogenic wind, cold, dampness, summer heat, dryness, and fire. Ancient and modern TCM physicians have a similar understanding that the occurrence of cancer is related to toxin. In the 1990s, the thought of cancerous toxin was first proposed by Prof Zhou Zhongying, a TCM master based on more than 60 years of clinical practice, who used “pandemic Qi (Li-Qi) is a specific pathogenic factor of epidemic disease” in Wenyi Lun (Treatise on Pestilence) for references. The pathogenesis theory of cancerous toxin was gradually established under the guidance of the thought of cancerous toxin. It holds that the cancerous toxin, a special pathogenic factor of cancer, is the key pathogenesis of the occurrence of malignant tumors. According to the pathogenesis theory of cancerous toxin, the basic pathogenesis of malignant tumors is the accumulation of pathogenic factors and cancerous toxin, and the deficiency of the vital Qi (Zheng-Qi). Therefore, the treatment principle involves eliminating pathogenic factors, resolving cancerous toxin, and supporting the vital Qi. The anticancer detoxification methods and the classification of Chinese medicinal herbs with anticancer detoxification effects were put forward. System theory has much in common with the concepts in the theory system of TCM, such as the universal relation theory, asking for a concrete analysis of concrete conditions, the humanism thought, and so on. This article aims to describe, review, and analyze the pathogenesis theory of cancerous toxin based on system theory for clinical practices.